Analisis Pengaruh Content Marketing, Social Media Marketing Dan Online Convenience Pada Consumer Buying Decision Process (Universitas Gresik, 2023)
The consumption of chicken meat in Indonesia continues to increase, and this increase is directly proportional to the increasing growth rate of the fast food restaurant industry, especially fried chicken product as one of the main commodities which ranks first as the food menu most frequently ordered by the public. However, from the list of the 5 most popular brands of fast food restaurants and fried chicken products in Indonesia, not a single Indonesian’s local brand is included in the list. Therefore, a strategy is needed to deal with competition, namely by increasing the company’s ability to adapt information technology for online product promotion and marketing purposes, by improving the quality of content marketing, social media marketing and online convenience, which is expected to improve the consumer buying decision process. Therefore, the purpose of this study is in order to analyze the effects of content marketing, social media marketing and online convenience on the consumer buying decision process for restaurant customers at Suharti’s fried chicken outlets in Jakarta. This research method is descriptive quantitative which is used to describe the influences between research variables based on the use of statistical analysis and mathematical equations. The source of the data is obtained through an online and offline questionnaire surveys of 180 customers of the Suharti’s fried chicken outlet restaurant in Jakarta, using non-probabilty sampling method and purposive sampling technique. The data analysis technique used is the Structural Equation Model (SEM) to test the research hypotheses. The findings of this study show that there are positive effects of content marketing, social media marketing and online convenience on the consumer buying decision process for restaurant customers at Suharti’s fried chicken outlets in Jakarta